La croissance sans limite : un paradigme américain proche de sa fin ? - Pierre Arnaud (Revue LISA)
Due to the specific circumstances of its early development, the US perceives the economy as an open, unlimited field. This results in behaviors, especially in the realm of consumption and debt, which boost the economy, favor growth and rebounds after a recession. However, this process is sustainable only because of the international role of the dollar, which draws part of the savings of the world to America. The ascent of China and other emerging powers could, in the long term, challenge the domination of the dollar. The upheaval resulting from this would not just be economic. Some the US cultural fundamentals would also be at stake.